Diseño de una herramienta de registro y digitalización de defectos presentes en el área de ajuste de la empresa Auteco S.A.S (2024)
Within the operational headquarters, a great diversity of processes are carried out in different work areas, for this project the operation of the adjustment area of the company was taken as a reference. This area is mainly in charge of evaluating and correcting those parts that present any defect or nonconformity. One of the activities carried out in this area is that the registration of this information is done manually, and its respective evidence is shown through a WhatsApp line or chat. All the information recorded is stored in digital media in temporalities after the day of registration. There is an opportunity for improvement in this regard, which stems from the difficulty in making decisions due to an inefficient flow of information that limits the ability to respond in real time to the defects that have been occurring. This is why the requirement provided by the company refers to improve the process of recording defects in the adjustment area and that the tool used for this improvement is adapted to the applications with which operators are familiar. On the other hand, the proposed solution to address this issue consists of the creation of three products, which are considered the main stages of the design, each with various associated activities and tasks. The three products are summarized below: • Microsoft Forms: A form was implemented using Microsoft Forms to facilitate the efficient digitization of information. This form allows for the collection of both manually entered data and photographs of defects sent via WhatsApp. • Excel: Using Power Automate, an information flow was established that allows the collected information to be sent directly to the storage system, in this case Excel. This ensures that the data is recorded in real time in the Excel file. • Power BI: Finally, a dashboard or report was created using the Power BI tool. In addition to showing some related indicators, this report presents a heat map graph highlighting the areas of the motorcycle with the most defects. All of this required both the application of knowledge acquired in subjects such as: Operations Strategy, Productivity Engineering, Data Science, Ergonomics, as well as the knowledge achieved in the realization of the project such as: data management, Power Automate, Power BI